2021
DOI: 10.3390/ijms22147650
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Tissue Characterization in Heart Failure with Preserved Ejection Fraction: From Histopathology and Cardiac Magnetic Resonance Findings to Therapeutic Targets

Abstract: Heart failure with preserved ejection fraction (HFpEF) is a complex clinical syndrome responsible for high mortality and morbidity rates. It has an ever growing social and economic impact and a deeper knowledge of molecular and pathophysiological basis is essential for the ideal management of HFpEF patients. The association between HFpEF and traditional cardiovascular risk factors is known. However, myocardial alterations, as well as pathophysiological mechanisms involved are not completely defined. Under the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 209 publications
(401 reference statements)
0
12
0
Order By: Relevance
“…A significant proportion of heart failure with reduced ejection fraction (HFrEF) patients have cardiovascular implantable electronic devices (CIED), compared to HFpEF patients, who are much more rarely invasively telemonitored. HFpEF patients are an aged population with high mortality and hospitalization rates, representing an ever-growing population in the HF spectrum [ 36 , 37 ]. For these reasons, telemedicine approaches through telephone consultations or other external devices may be particularly beneficial for HFpEF patients.…”
Section: Discussionmentioning
confidence: 99%
“…A significant proportion of heart failure with reduced ejection fraction (HFrEF) patients have cardiovascular implantable electronic devices (CIED), compared to HFpEF patients, who are much more rarely invasively telemonitored. HFpEF patients are an aged population with high mortality and hospitalization rates, representing an ever-growing population in the HF spectrum [ 36 , 37 ]. For these reasons, telemedicine approaches through telephone consultations or other external devices may be particularly beneficial for HFpEF patients.…”
Section: Discussionmentioning
confidence: 99%
“…Despite a normal LVEF, this patient has a low cardiac output, and his prognosis is related to several consequences, such as renal impairment and respiratory infections. In fact, the term preserved ejection fraction seems reassuring, but it hides energetic, structural and functional heart abnormalities [23,24]. Of note, LVEF-based classification it is not closely related to HF prognosis, and often, HFpEF patients show worse outcomes than HFrEF's group, with increased mortality and hospitalisation [10].…”
Section: Nyha Class Evolution Stages Phenotypesmentioning
confidence: 99%
“…Recent study found that intensive sympatho-excitation leads to pathological cardiac hypertrophy and fibrosis, which is coupled with decreased UPRmt and increased mitochondrial proteotoxic stress ( 80 ). These myocardial morphological alterations is closely associated with heart failure with preserved ejection fraction (HFpEF) ( 81 ). Smyrnias et al demonstrated that UPRmt is activated during chronic pressure overload and pharmacological enhancement of the UPRmt alleviates mitochondrial and contractile dysfunction in the stressed heart ( 82 ).…”
Section: Dysregulation Of Mitochondrial Proteostasis In Heart Failurementioning
confidence: 99%